Managing the tensions between luxury and sustainability : the case of the luxury hotels - Serradas, Maria Margarida Moreira Rato (2022)
Sustainability is increasingly becoming crucial for every business to stay competitive, resulting in various changes in the way companies operate. However, these changes can be quite challenging for luxury hotels since luxury and sustainability have contradictory aspects. This study focuses on how luxury hotels are adopting sustainable practices. To answer the research question, I conducted a comparative case study. The results show that the luxury hotels studied implemented eight main sustainable practices: managing waste, reducing the consumption of materials, having a sustainable cuisine and organic gardens, reducing the energy and water consumption, sourcing locally, making charity donations, supporting the community, and educating consumers on sustainability; along with the means to achieve them. Nevertheless, the implementation of these practices may negatively affect the guest’s experience in the sense that becoming more sustainable can compromise the luxurious experience guests expect. Thus, the contradictions between luxury and sustainable practices are also discussed and presented. This study provides theoretical knowledge while presenting practical recommendations and warnings for managers of luxury hotels who want to embrace sustainability in their business.